Incisional hernia repair in women of childbearing age: A nationwide propensity-score matched study. (December 2020) - Oma, E.; Jensen, K. K.; Jorgensen, L. N.; Bisgaard, T.
Background & Aims: Although incisional hernia repair in women of childbearing age is not rare, hernia disease in this group of patients is sparsely documented. The aim of this study was to examine long-term clinical results after incisional hernia repair in women of childbearing age. Material and methods: This nationwide cohort study examined incisional hernia repair from 2007 to 2013 in women of childbearing age, registered prospectively in the Danish Ventral Hernia Database. All women with a subsequent pregnancy were included, and a 1:3 propensity-score matched group of women with an incisional hernia repair without a subsequent pregnancy. A prospective follow-up was conducted, including a validated questionnaire. The primary outcome was recurrence, and the secondary outcome was chronic pain from the operated site. Results: In total, 124 (70.5%) women responded, 47 and 77 women with and without a subsequent pregnancy, respectively. The 5-year cumulative incidence of recurrence was 41.0% (95% confidence interval 32.0%–49.9%). After adjustment for potential confounders, subsequent pregnancy was independently associated with recurrence (hazard ratio 1.83, 95% confidence interval 1.02–3.29, p = 0.044). Twenty-six (21.0%) women reported chronic pain (moderate, n = 21; severe, n = 5) with no difference between women with and without a subsequent pregnancy. Hernia recurrence, higher body mass index, and smoking were associated with chronic pain. Conclusion: Pregnancy following incisional hernia repair was associated with an increased risk of recurrence, but not with chronic pain.